Recording Frequency-following Responses to Voice Pitch in Guinea Pigs: Preliminary Results. Issue 3 (June 2014) - Chou, Meng-Shih; Lin, Chia-Der; Wang, Tang-Chuan; Jeng, Fuh-Cherng
Although scalp-recorded frequency-following response (FFR) to voice pitch has shown great potential to examine pitch processing mechanisms in human participants and animals, few reports have addressed the test-retest reliability of such a response in an animal model. The purpose of this study was to investigate the feasibility and reliability of recording such a response in an animal model and to evaluate the extent to which the response could be separated from background noise. A Chinese monosyllable with a rising pitch was used to elicit the FFR to voice pitch in four guinea pigs. Four objective measures (Root-Mean-Square, Amplitude, Tracking Accuracy, Frequency Error, and Slope Error) were computed from recorded brain waves and were used to examine the phase-locking magnitude and test-retest reliability of the response. Results demonstrated that the animal model produced FFR trends that were repeatable, reliable, and significantly different from responses to the background noise.